EFFECTIVENESS OF CRITICAL MULTILITERATION MODEL WITH RADEC MODEL ON THE ABILITY OF WRITING EXPLANATORY TEXT - Dadan Setiawan; Tatat Hartati; Wahyu Sopandi (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2020)
Abstract: Developing students' skill in writing scientific explanation is one of the main goals in education. The purpose of this study is to determine the effectiveness of the critical multi-literation model and the RADEC model on the ability in writing explanatory text of elementary school students. This research is conducted on 5th grade students of SDN 122 Cijawura, Buah Batu, Bandung. The samples used in this study are 39 students in the experimental class 1 that used the critical multi-literation model and 38 students in the experimental class 2 that used the RADEC model. The research method used in this study is a quasi-experimental method with a non-equivalent pre-test and post-test control group design. Based on the results of the study, it is found that the pre-test score in the experimental class 1 is 36.6 and the post-test result is 78. Whereas in the experimental class 2 the pre-test score obtained is 48.1 and the post-test score is 68.9. Furthermore, from the results of the independent sample test, the results of the post-test mean difference test are sig = 0.018, so it can be concluded that there are significant differences in the ability to write explanatory text of students between the experimental class 1 and the experimental class 2. Based on these results, the multi-literation model critical is more effective than the RADEC model in developing the ability in writing explanatory text in elementary school students.